2009
DOI: 10.1111/j.1468-2427.2009.00831.x
|View full text |Cite
|
Sign up to set email alerts
|

Precarious Work and Economic Migration: Emerging Immigrant Divisions of Labour in Greater London's Service Sector

Abstract: The aim of this article is to assess the connections between the continued expansion of forms of insecure work and the impact of rising numbers of economic migrants employed in UK labour markets. It shows how competition between foreign-born workers for jobs in the UK is currently being recast by changes in the jobs available, in forms of precarious labour market attachment and by new patterns of migration into the UK since EU expansion in 2004. The article documents the ways in which migrants with different s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
163
0
11

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(181 citation statements)
references
References 58 publications
7
163
0
11
Order By: Relevance
“…Today’s global, capitalist labour system is not only hierarchically organized and geographically differentiated, it is also racialized and gendered, and exploits workers based on their social position [81,82]. Migrant workers are in a particularly vulnerable situation, as they are newcomers who are less familiar with the labour market, and often also have fewer rights [83]. Precarious work may have detrimental effects on health [84], and the lawless situation many undocumented workers are in also often produces negative effects on health and access to health care [85].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Today’s global, capitalist labour system is not only hierarchically organized and geographically differentiated, it is also racialized and gendered, and exploits workers based on their social position [81,82]. Migrant workers are in a particularly vulnerable situation, as they are newcomers who are less familiar with the labour market, and often also have fewer rights [83]. Precarious work may have detrimental effects on health [84], and the lawless situation many undocumented workers are in also often produces negative effects on health and access to health care [85].…”
Section: Resultsmentioning
confidence: 99%
“…Rosa said in the interview that she believed that part of the reason for her good experiences from working in Costa Rica was related to her ‘whiteness’ – that is, her pale skin colour made her look more Costa Rican than Nicaraguan, which meant that she did not have to endure as much xenophobia as other Nicaraguans. This shows that social position – for example, legal status, gender and ethnicity/‘race’ – influence the degree of precariousness and vulnerability for the migrant worker [83]. …”
Section: Resultsmentioning
confidence: 99%
“…These flows are gendered and racialized. Linda McDowell et al (2009) illustrated this through an ethnographic study of the working conditions at a hotel and a hospital in London. The authors showed that local developments, such as the increasing use of "exploitative, non-standard labor contracts" in the expanding service economy in the London area, used to "meet peaks and demands for workers," correspond to new migratory flows across Europe and the world.…”
Section: Intersectionality and Workmentioning
confidence: 99%
“…Migrants are as a group disproportionately concentrated in precarious and low-wage work and tend to cluster in certain low-skilled sectors and occupations (Wills et al 2010;Piore 1979). This has led to the emergence of new migrant divisions of labour at the bottom end of the labour market, depending on migrants' legal status and racial distinctions (Wills et al 2010;May et al 2007;McDowell et al 2009). It has been argued that the very availability of migrant workers, who can and are willing to work for lower rates, constructs labour markets that are increasingly dependent on migrants (McDowell et al 2009: 7;Favell 2008;Castells 1975;Bauder 2006).…”
Section: Cross-border Employment Relations In Europementioning
confidence: 99%
“…The contractual status of TWA workers is short-term and insecure, as they can 'be fired as quickly as they are hired' (Sporton 2013: 450). Although subcontractors and TWAs are formally bound by (minimum provisions of) the legally extended sectoral collective agreements in the Netherlands, non-compliances and irregularities in working conditions are 7 I use the term precarious, instead of flexible, to denote the fluidity and uncertainty that this type of work entails for workers (Kalleberg 2009;Anderson 2010;McDowell et al 2009). common, especially further down contracting chains. TWA employment and labour-only subcontracting embed migrants in a triangular relationship with a client firm and a TWA, where the actual work relation with the former is separated from the contractual employment relation with the latter (Smith 2010;Peck et al 2005).…”
Section: Cross-border Employment Relations In Europementioning
confidence: 99%